2013
DOI: 10.1039/c3ib40085a
|View full text |Cite
|
Sign up to set email alerts
|

The mouse retina in 3D: quantification of vascular growth and remodeling

Abstract: The mouse retina has become a prominent model for studying angiogenesis. The easy access and well-known developmental progression have significantly propelled our ability to examine and manipulate blood vessels in vivo. Nonetheless, most studies have restricted their evaluations to the superficial plexus (an upper vascular layer in contact with the vitreous). Here we present experimental data and quantification for the developmental progression of the full retina including the intermediate and deeper plexus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 47 publications
1
61
0
Order By: Relevance
“…Deletion also had no effect on angiogenesis in the aorta ring assay. Consistent with these findings, a previous study (43) found that formation of the outer retinal plexus appeared normal in Clic4 Ϫ/Ϫ mice during (P4) and near the end (P7) of the radial outgrowth phase, a phase dominated by angiogenic sprouting and capillary plexus formation (9,25), although the leading edge of the plexus tended to reach the outer retinal margin slightly later. However, on P21 the mature capillary bed had a lower number of branch points and overall vessel density (43).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Deletion also had no effect on angiogenesis in the aorta ring assay. Consistent with these findings, a previous study (43) found that formation of the outer retinal plexus appeared normal in Clic4 Ϫ/Ϫ mice during (P4) and near the end (P7) of the radial outgrowth phase, a phase dominated by angiogenic sprouting and capillary plexus formation (9,25), although the leading edge of the plexus tended to reach the outer retinal margin slightly later. However, on P21 the mature capillary bed had a lower number of branch points and overall vessel density (43).…”
Section: Discussionsupporting
confidence: 73%
“…However, on P21 the mature capillary bed had a lower number of branch points and overall vessel density (43). Maturation of the early retinal plexus into artery and vein trees and intervening capillaries involves selective pruning and repatterning processes that occur concurrently with radial outgrowth and are complete by P15 (9,25). Our observation that CLIC4 is required for pruning and maturation of the nascent collateral circulation has analogy to the deficiencies in retinal vascular remodeling (43).…”
Section: Discussionmentioning
confidence: 80%
“…Distinct differences in vascular network morphology exist between tissue types, where, for example, vessels are aligned in parallel to muscle fibers but take on a radial organization in the retinal lumen (20). We hypothesized that tensile forces applied by and on the cells during network assembly play a central role in determining vascular network morphology and properties.…”
mentioning
confidence: 99%
“…The introduction of spatially varying SCE potentials, elliptically shaped potential functions or fixed bonds in-between SCEs could address these limitations. Ongoing work focuses on the coupling of particle model with experimental data [20,40,41] and the quantification of uncertainties in the force field following related work of our group on Molecular Dynamics [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important for future works to carefully calibrate such migration models with experimental data. Data from wound healing assays [20,40] or the growth of blood vessels in the mouse retina [41] could be used to fit parameters for the models and to quantify their uncertainties [6].…”
Section: Only Considering the Neighborhood Elements Of Different Cellmentioning
confidence: 99%